Financial Security in the Electricity Market: An Approach to Minimize Commercial Counterparties’ Risks - Filho, Ernani Teixeira Torres; Machayba, Luiz; Rosa, Pedro Souza; Balan, Mateus Henrique; Ramos, Dorel Soares; Castro, Roberto; Lazzareschi, Vitor Hugo (International Journal of Energy Economics and Policy, 2026)
The risk management mechanisms, safeguards, and guarantee schemes adopted in the Brazilian electricity market (BEM) have been insufficient to prevent systemic default. To manage this fragility, this study posits that BEM regulation should be modernized according to the principles of prudential risk that are followed by the world´s most critical financial systems (Basel Accord). The study employs a Minskyian approach to identify the financial risks involved in negotiating, registering, and settling contracts in the BEM. We also propose a model to assess and anticipate the evolution of energy trading agents’ market risks in Brazil for different forward spot price curves and bilateral trading prices scenarios. The model emulates agents’ expected trading behavior referencing historical microdata provided by the regulators for all market participants. We divide the companies into three groups of “personas”, based on the observed behavior of market agents to emulate real trading behavior in a virtual environment under simulated bilateral price trajectories and spot price forward curves. The model produces significant results for addressing traders’ bilateral risks. From this perspective, we identify previous stress circumstances and increased systemic risk, which can help regulators to prevent “domino effects.” The BEM faced credit difficulties at the end of 2000 and the beginning of 2001. We reproduce this real insolvency in the virtual environment, and the results demonstrate that this approach would be an effective tool to predict the situation at least six months before the involved agents’ default, representing one of the main results of the project: predictability.